Dyadic Interdependence in Non-spousal Caregiving Dyads’ Wellbeing: A Systematic Review - Ferraris, Giulia; Dang, Srishti; Woodford, Joanne; Hagedoorn, Mariët (Frontiers in Psychology, 2022)
Caregiving dyads (i.e., an informal caregiver and a care recipient) work as an interdependent emotional system, whereby it is assumed that what happens to one member of the dyad essentially happens to the other. For example, both members of the dyad are involved in care giving and care receiving experiences and major life events, such as a serious illness, affect the dyad and not only the individual. Consequently, informal caregiving may be considered an example of dyadic interdependence, which is “the process by which interacting people influence one another’s experience”. This systematic review aimed to synthesize studies of dyadic interdependence, specifically in non-spousal caregiving dyads (e.g., adult children – parents, siblings, other relatives or friends). Electronic databases (PsycINFO, Pubmed, and CINAHL) were systematically searched for dyadic studies that reported on the interdependence in the emotional and relational wellbeing of non-spousal caregiving dyads. A total of 239 full-text studies were reviewed, of which 14 quantitative and qualitative studies met the inclusion criteria with a majority of dyads consisting of adult daughters caring for their older mothers. A narrative synthesis suggested mutual influences between non-spousal caregiving dyad members based on: (1) associations between intrapersonal (e.g., psychological functioning) and interpersonal (e.g., relationship processes) variables and emotional and relational wellbeing of the dyad; (2) associations between care context variables (e.g., socio-demographics and care tasks) and emotional and relational wellbeing of the dyad; and (3) patterns of covariation between caregivers’ and care recipients’ wellbeing. Evidence supporting dyadic interdependence among non-spousal caregiving dyads shed light on the ways dyad members influence each other’s wellbeing while providing and receiving care (e.g., via the exchange of support). Future studies investigating mutual influences in dyads, should differentiate subsamples of caregivers based on relationship type, and adopt dyadic and longitudinal designs.